THE INCORRECTNESS OF ESTIMATING OF TAX BASE IN INCOME TAXES IN THE RESEARCH - Witczak, Radosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->The effect of transformation in Poland is tax evasion of income taxes. One way of diminishing the tax evasion is estimating of tax base. The provisions point out different methods of estimating of the tax base. The analyse of using the methods of estimating of tax base by the tax authorities was given. The scope of the analyse were different cases from the administrative court. The cases concerned different types of methods of tax estimation used by tax administration. In the majority of analysed cases the use of methods of estimating of tax base was correct. The implementation of rules concerning other methods of estimating of tax base was proposed.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->